Management of Infections in the Immunocompromised Host (Springer International Publishing, 2018)
This book provides a comprehensive, state-of-the-art review of the concepts vital to a modern treatment of common and opportunistic infections in the immunocompromised host. Chapters are written by experts in the field, and include their views on gaps in the field and future directions of research. This book begins with an overview of the normally functioning immune system followed by a detailed discussion of the major primary immunodeficiencies. Specific chapters are dedicated to providing practical knowledge in the prevention and treatment of infections in specific immunocompromised patients, including those with cancer, transplant recipients, HIV infection, and autoimmune disorders. Emphasis is placed on diagnostic evaluation, antimicrobial selection that includes consideration of the threat of antimicrobial-resistant pathogens, and immunotherapy tailored to specific patients. Finally, dedicated chapters on stem cell transplantation for patients with primary immunodeficiencies, adoptive cellular immunotherapy, and gene therapy will provide readers with insight into these rapidly evolving and cutting edge therapies. Management of Infections in the Immunocompromised Host is a valuable resource for infectious diseases specialists, immunologists, oncologists, hematologists, general physicians, students, researchers, and all other working with immunocompromised patients.